Copper-doped bismuth sulfide for antibacterial applications and methods of making and using the same
Patent Information
- Application Number
- CN202311188804.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-09-14
AI Technical Summary
然而其电子与空穴的复合速率过快从而导致光催化效率低,抗菌的效果不佳
[0017] In the preparation method of copper-doped bismuth sulfide for antibacterial purposes, copper-doped bismuth sulfide is obtained by selecting the type of precursor and controlling the mass ratio of the precursor to copper salt. The copper-doped bismuth sulfide consists of pea-shaped nanoparticles with grooves on the surface, with a diameter of 150 nm-200 nm and a copper doping rate of 0.2%-0.5%. By controlling the morphology, particle size, and copper doping rate of copper-doped bismuth sulfide, on the one hand, the electron density in the local area can be increased by increasing the electron delocalization degree of bismuth sulfide, thereby reducing the recombination rate of electrons and holes in bismuth sulfide; on the other hand, the electrons in bismuth sulfide can be transferred from the conduction band of bismuth sulfide to copper ions, which can effectively inhibit electron-hole recombination and prolong the electron-hole lifetime. Thus, bismuth sulfide has excellent photocatalytic activity and can effectively inhibit bacteria.
Smart Images

Figure CN117461653B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of antibacterial technology, and in particular to a copper-doped bismuth sulfide for antibacterial purposes, its preparation method, and its application. Background Technology
[0002] Agricultural productivity is threatened by various factors, such as water, climate, and soil. Among these, fungal pathogen infections are a major problem, limiting the yield of a range of crops. For example, apple anthracnose is a disease that primarily affects apple fruit. It occurs in all countries and regions suitable for apple cultivation worldwide, with a wide range of impacts. In epidemic years, the disease incidence rate can reach 30%-60%, causing apple fruit to rot and severely affecting both quality and yield. In recent years, the use of chemical pesticides has been an effective measure for controlling plant diseases and pests. However, the long-term use of some chemical pesticides has led to drug resistance in plant pathogens, resulting in increased pesticide dosages and decreased control effectiveness. Increased pesticide use poses serious risks to human health and the ecological environment. Therefore, there is an urgent need for low-toxicity, highly effective, and environmentally friendly control methods.
[0003] Bismuth sulfide (Bi₂S₃) is a broad-absorbing n-type semiconductor with advantages such as strong mechanical properties, good thermal stability, resistance to acid and alkali corrosion, and environmental friendliness. It can also kill pathogens through localized photothermal effects and the generation of reactive oxygen species, making it a potential photocatalytic material for killing pathogens. However, its excessively rapid electron-hole recombination rate leads to low photocatalytic efficiency and poor antibacterial effect. Summary of the Invention
[0004] Therefore, it is necessary to address the above problems by providing a copper-doped bismuth sulfide for antibacterial purposes, its preparation method, and its application. The copper-doped bismuth sulfide obtained by this preparation method has excellent photocatalytic activity and excellent inhibitory effect on pathogens.
[0005] A method for preparing copper-doped bismuth sulfide for antibacterial purposes includes the following steps:
[0006] Bismuth nitrate pentahydrate, thioacetamide, copper salt, and solvent are mixed to obtain a mixed solution, wherein the mass ratio of bismuth nitrate pentahydrate, thioacetamide, and copper salt is (45-50):(25-30):(0.1-0.4).
[0007] The mixed solution was subjected to a hydrothermal reaction to separate copper-doped bismuth sulfide. The morphology of the copper-doped bismuth sulfide was pea-shaped nanoparticles with grooves on the surface, with a diameter of 150 nm-200 nm and a copper doping rate of 0.2%-0.5%.
[0008] In one embodiment, the mass ratio of the bismuth nitrate pentahydrate, the thioacetamide, and the copper salt is (45-50):(25-30):(0.1-0.25).
[0009] In one embodiment, the mass ratio of the bismuth nitrate pentahydrate to the solvent is 45:50-50:70.
[0010] In one embodiment, the copper salt is selected from copper nitrate trihydrate.
[0011] In one embodiment, the solvent is selected from water.
[0012] In one embodiment, in the step of subjecting the mixed solution to a hydrothermal reaction, the reaction temperature is 150°C-170°C and the reaction time is 7h-9h.
[0013] A copper-doped bismuth sulfide for antibacterial purposes, prepared by the method described above, wherein the copper-doped bismuth sulfide has the morphology of pea-shaped nanoparticles with grooves on the surface, a diameter of 150 nm-200 nm, and a copper doping rate of 0.2%-0.5%.
[0014] In one embodiment, the copper doping rate of the copper-doped bismuth sulfide is 0.2%-0.3%.
[0015] In one embodiment, the copper-doped bismuth sulfide produces no copper atom diffraction peaks during X-ray diffraction.
[0016] A copper-doped bismuth sulfide, as described above, is used as an antibacterial agent.
[0017] In the preparation method of copper-doped bismuth sulfide for antibacterial purposes, copper-doped bismuth sulfide is obtained by selecting the type of precursor and controlling the mass ratio of the precursor to copper salt. The copper-doped bismuth sulfide consists of pea-shaped nanoparticles with grooves on the surface, with a diameter of 150 nm-200 nm and a copper doping rate of 0.2%-0.5%. By controlling the morphology, particle size, and copper doping rate of copper-doped bismuth sulfide, on the one hand, the electron density in the local area can be increased by increasing the electron delocalization degree of bismuth sulfide, thereby reducing the recombination rate of electrons and holes in bismuth sulfide; on the other hand, the electrons in bismuth sulfide can be transferred from the conduction band of bismuth sulfide to copper ions, which can effectively inhibit electron-hole recombination and prolong the electron-hole lifetime. Thus, bismuth sulfide has excellent photocatalytic activity and can effectively inhibit bacteria. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 The X-ray diffraction pattern of copper-doped bismuth sulfide for antibacterial purposes obtained in Example 1;
[0020] Figure 2 The UV-Vis absorption spectrum of copper-doped bismuth sulfide for antibacterial purposes obtained in Example 1 is shown.
[0021] Figure 3 The images are scanning electron microscope (SEM) images, where a and b are SEM images of bismuth sulfide obtained in Comparative Example 1, and c and d are SEM images of copper-doped bismuth sulfide for antibacterial purposes obtained in Example 1.
[0022] Figure 4 The figures are photocurrent test diagrams, where A is the photocurrent test diagram of copper-doped bismuth sulfide for antibacterial use obtained in Example 1, and B is the photocurrent test diagram of bismuth sulfide obtained in Comparative Example 1.
[0023] Figure 5 Here are impedance diagrams, where D is the impedance diagram of copper-doped bismuth sulfide for antibacterial use obtained in Example 1, and C is the impedance diagram of bismuth sulfide obtained in Comparative Example 1.
[0024] Figure 6 The images show the antibacterial activity of apple anthracnose bacteria under different light exposure times. F represents the antibacterial activity of PDA culture medium without additives under light exposure for 0 min, 15 min, 30 min, 45 min, and 60 min. H represents the antibacterial activity of copper-doped bismuth sulfide obtained in Example 1 under light exposure for 0 min, 15 min, 30 min, 45 min, and 60 min. G represents the antibacterial activity of bismuth sulfide obtained in Comparative Example 1 under light exposure for 0 min, 15 min, 30 min, 45 min, and 60 min. Detailed Implementation
[0025] To facilitate understanding of the present invention, a more complete description will be given below with reference to relevant embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all the related listed items.
[0027] This invention provides a method for preparing copper-doped bismuth sulfide for antibacterial purposes, comprising the following steps:
[0028] S1, bismuth nitrate pentahydrate, thioacetamide, copper salt and solvent are mixed to obtain a mixed solution, wherein the mass ratio of bismuth nitrate pentahydrate, thioacetamide and copper salt is (45-50):(25-30):(0.1-0.4);
[0029] S2, the mixed solution is subjected to a hydrothermal reaction to separate copper-doped bismuth sulfide. The morphology of the copper-doped bismuth sulfide is pea-shaped nanoparticles with grooves on the surface, with a diameter of 150nm-200nm and a copper doping rate of 0.2%-0.5%.
[0030] In step S1, bismuth nitrate pentahydrate and thioacetamide are used as bismuth sulfide precursors, and copper salt is used as a dopant source. After mixing, copper-doped bismuth sulfide can be obtained through a subsequent hydrothermal reaction.
[0031] In one embodiment, the copper salt is selected from copper nitrate trihydrate, and the solvent is selected from water, preferably pure water.
[0032] In order to better generate copper-doped bismuth sulfide in the subsequent hydrothermal reaction, in one embodiment, the mass ratio of the bismuth nitrate pentahydrate, the thioacetamide and the copper salt is (45-50):(25-30):(0.1-0.25).
[0033] In one embodiment, the mass ratio of the bismuth nitrate pentahydrate to the solvent is 45:50-50:70.
[0034] In order to better mix bismuth nitrate pentahydrate, thioacetamide and copper salt evenly, in one embodiment, the preferred method for mixing bismuth nitrate pentahydrate, thioacetamide and copper salt and solvent is stirring, and the stirring time is 11h-12h.
[0035] In step S2, bismuth nitrate pentahydrate and thioacetamide in the mixed solution undergo a hydrothermal reaction, dissolving at high temperature and recrystallizing to generate bismuth sulfide with a pea-shaped nanoparticle morphology and grooved surface. Additionally, copper salt in the mixed solution dissolves and is incorporated into the bismuth sulfide during recrystallization, resulting in copper-doped bismuth sulfide. By controlling the mass ratio of bismuth nitrate pentahydrate, thioacetamide, and the copper source, the diameter, morphology, and copper doping rate of the generated copper-doped bismuth sulfide can be controlled.
[0036] By controlling the diameter, morphology, and copper doping rate of copper-doped bismuth sulfide, two effects can be achieved: firstly, increasing the electron delocalization of bismuth sulfide can improve the local electron density, thereby reducing the recombination rate of electrons and holes in bismuth sulfide; secondly, transferring electrons from the conduction band of bismuth sulfide to copper ions can effectively inhibit electron-hole recombination and prolong the electron-hole lifetime, thus giving bismuth sulfide excellent photocatalytic activity and effective antibacterial properties. Furthermore, copper is inexpensive and readily available, and its compounds have low toxicity and are environmentally friendly, which is conducive to its industrial application.
[0037] In order to make the hydrothermal reaction more complete, in one embodiment, the reaction temperature is 150℃-170℃ and the reaction time is 7h-9h during the hydrothermal reaction of the mixed solution.
[0038] In order to better separate copper-doped bismuth sulfide from the product, in one embodiment, the separation method is preferably centrifugation in the step of separating copper-doped bismuth sulfide.
[0039] Understandably, after the separation step, there is also a drying step, with the drying temperature preferably being 50℃-60℃ and the drying time preferably being 5h-6h.
[0040] The present invention also provides a copper-doped bismuth sulfide for antibacterial purposes, prepared by the method described above. The morphology of the copper-doped bismuth sulfide is pea-shaped nanoparticles with grooves on the surface, with a diameter of 150 nm-200 nm and a copper doping rate of 0.2%-0.5%. In this case, electrons in the copper-doped bismuth sulfide are transferred from the conduction band of bismuth sulfide to copper ions, which can effectively inhibit electron-hole recombination and prolong the electron-hole lifetime, thereby exhibiting excellent photocatalytic activity and effectively inhibiting bacteria.
[0041] For better antibacterial properties, preferably, the copper doping rate of the copper-doped bismuth sulfide is 0.2%-0.3%.
[0042] In one embodiment, no copper atom diffraction peaks are generated during X-ray diffraction of the copper-doped bismuth sulfide, indicating that copper atoms are uniformly dispersed in the bismuth sulfide.
[0043] Furthermore, the present invention can use the copper-doped bismuth sulfide described above for antibacterial purposes as an antibacterial agent, such as an anti-anthrax agent for apples. Because the copper-doped bismuth sulfide used for antibacterial purposes has excellent photocatalytic activity, it can effectively inhibit the growth of pathogens, thus exhibiting excellent antibacterial effects when used as an antibacterial agent.
[0044] The following specific examples will further illustrate the copper-doped bismuth sulfide for antibacterial purposes, its preparation method, and its application.
[0045] Example 1
[0046] Mix 50 mg of bismuth nitrate pentahydrate with 50 mL of pure water and sonicate for 20 min. Then, add 0.15 mg of copper nitrate trihydrate during sonication and stir for 15 min. Add 27 mg of ammonium thioacetate and continue stirring for 12 h to obtain a mixed solution.
[0047] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel, and the reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled, and the reactants were centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain copper-doped bismuth sulfide, which has the morphology of pea-shaped nanoparticles with grooves on the surface, a diameter of 160 nm, and a copper doping rate of 0.2%.
[0048] The X-ray diffraction pattern of the copper-doped bismuth sulfide obtained in this embodiment is as follows: Figure 1 As shown, by Figure 1 As can be seen, the copper-doped bismuth sulfide sample shows all the diffraction peaks of bismuth sulfide, and the copper-doped component has no signal in the spectrum, indicating that the copper atoms are uniformly dispersed in the material.
[0049] The UV-Vis absorption spectrum of the copper-doped bismuth sulfide obtained in this embodiment is as follows: Figure 2 As shown, by Figure 2 It can be seen that copper-doped bismuth sulfide has a wide light absorption range.
[0050] Example 2
[0051] Mix 50 mg of bismuth nitrate pentahydrate with 50 mL of pure water and sonicate for 20 min. Then, add 0.23 mg of copper nitrate trihydrate during sonication and stir for 15 min. Add 27 mg of ammonium thioacetate and continue stirring for 12 h to obtain a mixed solution.
[0052] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel, and the reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled, and the reactants were centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain copper-doped bismuth sulfide, which has the morphology of pea-shaped nanoparticles with grooves on the surface, a diameter of 165 nm, and a copper doping rate of 0.3%.
[0053] Example 3
[0054] Mix 50 mg of bismuth nitrate pentahydrate with 50 mL of pure water and sonicate for 30 min. Then, add 0.23 mg of copper chloride during sonication and stir for 20 min. Add 27 mg of ammonium thioacetate and continue stirring for 12 h to obtain a mixed solution.
[0055] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel, and the reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled, and the reactants were centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain copper-doped bismuth sulfide, which has the morphology of pea-shaped nanoparticles with grooves on the surface, a diameter of 165 nm, and a copper doping rate of 0.3%.
[0056] Example 4
[0057] Mix 50 mg of bismuth nitrate pentahydrate with 50 mL of pure water and sonicate for 20 min. Then, add 0.308 mg of copper nitrate trihydrate during sonication, stir for 15 min, add 27 mg of ammonium thioacetate, and continue stirring for 12 h to obtain a mixed solution.
[0058] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel, and the reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled, and the reactants were centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain copper-doped bismuth sulfide, which has the morphology of pea-shaped nanoparticles with grooves on the surface, a diameter of 165 nm, and a copper doping rate of 0.4%.
[0059] Example 5
[0060] Mix 50 mg of bismuth nitrate pentahydrate with 50 mL of pure water and sonicate for 20 min. Then, add 0.385 mg of copper nitrate trihydrate during sonication and stir for 15 min. Add 27 mg of ammonium thioacetate and continue stirring for 12 h to obtain a mixed solution.
[0061] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel, and the reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled, and the reactants were centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain copper-doped bismuth sulfide, which has the morphology of pea-shaped nanoparticles with grooves on the surface, a diameter of 165 nm, and a copper doping rate of 0.5%.
[0062] Comparative Example 1
[0063] Mix 50 mg of bismuth nitrate pentahydrate with 50 mL of pure water, sonicate for 20 min, add 27 mg of ammonium thioacetate, and continue stirring for 12 h to obtain a mixed solution.
[0064] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel, and the reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled, and the reactants were centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain bismuth sulfide, which has the morphology of pea-shaped nanoparticles with grooves on the surface.
[0065] Scanning electron microscope (SEM) images of copper-doped bismuth sulfide obtained in Example 1 and bismuth sulfide obtained in Comparative Example 1 are shown below. Figure 3 As shown, by Figure 3 It can be seen that copper doping did not affect the morphology of the bismuth sulfide matrix.
[0066] The photocurrent test patterns of copper-doped bismuth sulfide obtained in Example 1 and bismuth sulfide obtained in Comparative Example 1 are shown below. Figure 4 As shown, by Figure 4 It can be seen that the electron-hole pair separation efficiency of the copper-doped bismuth sulfide obtained in Example 1 is significantly higher than that of the bismuth sulfide obtained in Comparative Example 1.
[0067] The impedance diagrams of copper-doped bismuth sulfide obtained in Example 1 and bismuth sulfide obtained in Comparative Example 1 are shown below. Figure 5 As shown, by Figure 5 It can be seen that the copper-doped bismuth sulfide obtained in Example 1 has a lower impedance.
[0068] Comparative Example 2
[0069] Mix 50 mg of bismuth chloride with 50 mL of pure water and sonicate for 30 min. Then, add 0.23 mg of copper nitrate trihydrate during sonication, stir for 20 min, add 27 mg of thiourea, and continue stirring for 12 h to obtain a mixed solution.
[0070] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel. The reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled. The reactants were then centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain copper-doped bismuth sulfide with a copper doping rate of 0.3%.
[0071] Comparative Example 3
[0072] Mix 50 mg of bismuth nitrate pentahydrate with 50 mL of pure water and sonicate for 20 min. Then, add 0.462 mg of copper nitrate trihydrate during sonication, stir for 15 min, add 27 mg of ammonium thioacetate, and continue stirring for 12 h to obtain a mixed solution.
[0073] The above mixed solution was placed into a 100 mL polytetrafluoroethylene reaction vessel. The reaction vessel was placed in an oven for hydrothermal reaction at a temperature of 160 °C for 8 h. After the reaction was completed, the reaction vessel was cooled. The reactants were then centrifuged multiple times with pure water and ethanol to obtain a black solid precipitate. Finally, the solid precipitate was dried at 60 °C to obtain copper-doped bismuth sulfide with a copper doping rate of 0.6%.
[0074] Test Example 1
[0075] The copper-doped bismuth sulfide obtained in Example 1 and the bismuth sulfide obtained in Comparative Example 1 were subjected to a photocatalytic anti-anthrax experiment on apples. The specific process is as follows:
[0076] Bismuth sulfide obtained in Comparative Example 1 and copper-doped bismuth sulfide obtained in Example 1 were used as additives and dispersed separately in PDA (potato dextrose agar) medium (additive concentration: 0.1 mg / mL) using ultrasound to prepare solutions. Apple anthracnose fungus was inoculated into both PDA medium without additives and the aforementioned PDA medium with additives, respectively. Irradiation was performed using a xenon lamp with a spectrum of 420 nm and a power of 300 W, equipped with a filter. The illumination times for each group were 0 min, 15 min, 30 min, 45 min, and 60 min, respectively. After illumination, the medium was placed in an incubator at a controlled temperature of 26 °C and cultured for 3 days. Mycelial growth was observed and recorded.
[0077] Mycelial growth as follows Figure 6As shown in the figure, after 3 days, in the PDA medium without additives, the mycelia completely filled the medium regardless of whether there was light exposure; in the PDA medium with bismuth sulfide additives, the mycelia completely filled the medium without light exposure, and the mycelial growth slowed down slightly after light exposure, but the slowdown was slow; in the medium with copper-doped bismuth sulfide, the mycelia still completely filled the medium without light exposure, but the mycelial growth slowed down significantly after light exposure. This indicates that copper doping can enhance the photocatalytic activity of bismuth sulfide, and copper-doped bismuth sulfide with a copper doping rate of 0.3% completely inhibited mycelial growth after 45 minutes of light exposure. Therefore, copper-doped bismuth sulfide with a copper doping rate of 0.3% has the best antibacterial effect.
[0078] The copper-doped bismuth sulfide obtained in Examples 1-5, the bismuth sulfide obtained in Comparative Example 1, and the copper-doped bismuth sulfide obtained in Comparative Examples 2-3 were used as additives and subjected to an antibacterial experiment against apple anthracnose using the above method. The light exposure time was 45 min, and the antibacterial rate was tested after 3 days of growth. The test method is as follows, and the test results are shown in Table 1:
[0079] Inhibition rate (%) = (Coronary diameter of control group - Colony diameter of treatment group) / (Coronary diameter of control group - Diameter of mycelial cake) × 100%. Wherein the control group is PDA medium without additives, and the treatment group is PDA medium with copper-doped bismuth sulfide obtained in Examples 1-5, bismuth sulfide obtained in Comparative Example 1, and copper-doped bismuth sulfide obtained in Comparative Examples 2-3 respectively.
[0080] Table 1
[0081] Example 1 97.56 Example 2 100 Example 3 98.64 Example 4 97.16 Example 5 95.68 Comparative Example 1 73.52 Comparative Example 2 92.38 Comparative Example 3 90.46
[0082] As shown in Table 1, the antibacterial rate of the copper-doped bismuth sulfide of the present invention can reach 100%. Furthermore, according to the examples and comparative examples, the copper doping rate of the copper-doped bismuth sulfide of the present invention, at 0.2%-0.5%, exhibits excellent antibacterial effect against *Amanita fulvidracoides*, the causal agent of apple anthracnose, and the antibacterial effect is even better when the copper doping rate is 0.2%-0.3%. Therefore, the copper-doped bismuth sulfide of the present invention has a highly efficient antibacterial effect.
[0083] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0084] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing copper-doped bismuth sulfide for antibacterial purposes, characterized in that, Includes the following steps: Bismuth nitrate pentahydrate, thioacetamide, copper salt, and solvent are mixed to obtain a mixed solution, wherein the mass ratio of bismuth nitrate pentahydrate, thioacetamide, and copper salt is (45-50):(25-30):(0.1-0.25). The mixed solution was subjected to a hydrothermal reaction to separate copper-doped bismuth sulfide. The morphology of the copper-doped bismuth sulfide was pea-shaped nanoparticles with grooves on the surface, with a diameter of 150 nm-200 nm and a copper doping rate of 0.2%-0.5%.
2. The method for preparing copper-doped bismuth sulfide for antibacterial purposes according to claim 1, characterized in that, The mass ratio of the bismuth nitrate pentahydrate to the solvent is 45:50-50:
70.
3. The method for preparing copper-doped bismuth sulfide for antibacterial purposes according to claim 1, characterized in that, The copper salt is selected from copper nitrate trihydrate.
4. The method for preparing copper-doped bismuth sulfide for antibacterial purposes according to claim 1, characterized in that, The solvent is selected from water.
5. The method for preparing copper-doped bismuth sulfide for antibacterial purposes according to claim 1, characterized in that, In the step of carrying out the hydrothermal reaction of the mixed solution, the reaction temperature is 150℃-170℃ and the reaction time is 7h-9h.
6. A copper-doped bismuth sulfide for antibacterial purposes, obtained by the preparation method according to any one of claims 1-5, characterized in that, The copper-doped bismuth sulfide has the morphology of pea-shaped nanoparticles with grooves on the surface, with a diameter of 150nm-200nm and a copper doping rate of 0.2%-0.5%.
7. The copper-doped bismuth sulfide for antibacterial purposes according to claim 6, characterized in that, The copper doping rate of the copper-doped bismuth sulfide is 0.2%-0.3%.
8. The copper-doped bismuth sulfide for antibacterial purposes according to claim 6, characterized in that, The copper-doped bismuth sulfide produces no copper atom diffraction peaks during X-ray diffraction.
9. The use of copper-doped bismuth sulfide as an antibacterial agent as described in any one of claims 6-8.
Citation Information
Patent Citations
Near-infrared responsive antibacterial nano-composite coating and preparation method and application thereof
CN110591430A
Cu-doped bismuth sulfide material as well as preparation method and application thereof
CN114635159A